MASALAH USAHA SARANG BURUNG WALET TEHADAP PERATURAN PEMBANGUNAN DAN LINGKUNGAN HIDUP DI KOTA SAMARINDA - Gunawan Hasibuan (Universitas 17 Agustus 1945 Samarinda, 2014)
AbstractThe crisis is a situation that was a turning point that can make things better or worse added. However, behind the Indonesian economic crisis, many employers who exploit this situation to perform a variety of economic enterprises. One of the most prominent business today is the development of breeding birds nest wallet (shop) in the city center. Of the bird's saliva rather like gold or valuables. Valuable commodity always attract those who want to get wealth, especially for entrepreneurs Permission is an approval of the authorities by legislation or government regulation in certain circumstances, notwithstanding the prohibition laws. While understanding the licensing is a dispensation of a ban, usually using some basic laws permit such regions local regulations or decisions of the mayor, although in the end the decision is different in each area, but a lot of the same principles and rules, for example about the procedures and requirements completeness pengurusaan required .